KEBIASAAN SARAPAN DAN KONSENTRASI BELAJAR MAHASISWA - I Gede Purnawinadi; Christa Vike Lotulung (NUTRIX, 2020)
Breakfast is useful to meet the energy needs of the body, especially the brain requires nutrition in improving the ability to concentrate in learning. This study aims to analyze the relationship between breakfast habits and the concentration of learning in students at Klabat University. This type of research is an analytic survey through a cross sectional approach which was conducted on 177 general English 1 class students who were selected using a purposive sampling technique. The questionnaire was used to obtain data on breakfast habits and concentration of learning. Analysis of the relationship between variables using the Spearman Correlation test. The results showed that the dominant students rarely had breakfast (39%) and high learning concentration (56.5%). There was a very weak but significant relationship between breakfast habits with the level of student learning concentration (r = 0.162 and p = 0.031). Students awareness about the importance of breakfast needs to be increased through socialization in the classroom and outside the classroom. Keywords: breakfast habit, learning concentration, students Sarapan bermanfaat memenuhi kebutuhan energi tubuh terlebih otak memerlukan gizi dalam meningkatkan kemampuan konsentrasi dalam belajar. Penelitian ini bertujuan untuk menganalisis hubungan kebiasaan sarapan dengan konsentrasi belajar pada mahasiswa di Universitas Klabat. Jenis penelitian ini merupakan survei analitik melalui pendekatan cross sectional yang dilakukan pada 177 mahasiswa kelas general english 1 yang dipilih menggunakan teknik purposive sampling. Kuesioner digunakan untuk memperoleh data kebiasaan sarapan dan konsentrasi belajar. Analisis hubungan antar variabel menggunakan uji Korelasi Spearman. Hasil penelitian menunjukkan bahwa dominan mahasiswa jarang sarapan (39%) dan konsentrasi belajar tinggi (56,5%). Terdapat hubungan yang sangat lemah namun bermakna antara kebiasaan sarapan dengan tingkat konsentrasi belajar mahasiswa (r = 0,162 dan p = 0,031). Kesadaran mahasiswa tentang pentingnya sarapan perlu ditingkatkan melalui sosialisasi di kelas maupun di luar kelas. Kata kunci: kebiasaan sarapan, konsentrasi belajar, mahasiswa